PALM OIL EPOXIDATION CATALYZED BY EARLY TRANSITION METAL (Zr, V and Nb) - ASTAMAN HARAHAP - NIM: 20515026 , LHEILAMORA
Palm oil is fatty oil derived from palm plants. Palm oil is one of Indonesia foreign exchange contributors from plantation sectors. In 2015 the amount of palm oil production accounts for 54% of the world total production. The contribution of palm oil to Indonesia macroeconomics also depends on technologies of palm oil conversions into high-value products. One of which is through epoxidation reactions. Epoxidized products are important precursors in productions of plasticizers and stabilizers of polymers, lubricants, polyurethanes and emulsifiers, coating agents and other active compounds. Epoxidation reactions catalyzed by transition metals require the presence of an early transition metal with oxophilic properties and at least one oxo ligand to form an active species of peroxo metal. Selected metals in this research are V, Nb and Zr oxo, such as V2O5 (vanadium(V)), Nb2O5 (niobium(V)) and Zr(IV) MOF containing cluster of Zr6O4(OH)4. The three oxo compounds have a central metal with maximum oxidation state. A complex that may proceed a reaction involving a single electron transfer is vanadium(IV) complex, e.g., oxovanadium  -diketonates. An example of  -diketonate complexes is VO(acac)2. A catalytic study of immobilized VO(acac)2 in a Zr MOF was also studied. Catalytic tests were carried out by reacting palm oil (PO) or fatty acid ethyl ester (FAEE) as a source of olefin, catalyst, solvent and oxidizing agent for 5 h at 6 Ã‚Â°C. The product was characterized using 1H NMR and gas chromatography (GC). A methyn resonance of epoxide was observed at a chemical shift of 2.8 ppm (1H NMR). A new peak at 23 min in the GC chromatogram was suspected as an epoxide. This is supported by a decreasing ratio of oleic and linoleic area in the chromatogram relative to the corresponding palmitate. Palm oil epoxidations (50% conversion) were successfully carried out when it was catalyzed by VO(acac)2 using TBHP and toluene. FAEE epoxidations (80% conversion) were successfully carried out when it was catalyzed by VO(acac)2 using TBHP in the absence of solvent.